2022
DOI: 10.3934/eect.2020107
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control problems for a neutral integro-differential system with infinite delay

Abstract: <p style='text-indent:20px;'>This work devotes to the study on problems of optimal control and time optimal control for a neutral integro-differential evolution system with infinite delay. The main technique is the theory of resolvent operators for linear neutral integro-differential evolution systems constructed recently in literature. We first establish the existence and uniqueness of mild solutions and discuss the compactness of the solution operator for the considered control system. Then, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In practice, integrodifferential systems are always used to describe a model that has hereditary features, for more details, refer to articles. 10,11,19,20,24,28,32,[39][40][41][42] Currently, the authors of References 43-46 demonstrated fractional differential evolution systems of order 1 < đ›Œ < 2 using various fractional derivatives, sectorial operators of type (M, 𝜃, đ›Œ, 𝜇), measures of noncompactness, nonlocal conditions, and various fixed point techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, integrodifferential systems are always used to describe a model that has hereditary features, for more details, refer to articles. 10,11,19,20,24,28,32,[39][40][41][42] Currently, the authors of References 43-46 demonstrated fractional differential evolution systems of order 1 < đ›Œ < 2 using various fractional derivatives, sectorial operators of type (M, 𝜃, đ›Œ, 𝜇), measures of noncompactness, nonlocal conditions, and various fixed point techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A general formulation and solution scheme for fractional optimal control problems are discussed in Reference 18. The authors of References 19‐31 used impulsive systems, Clarke subdifferential type, neutral integrodifferential systems, Hilfer fractional derivative, stochastic systems, Riemann–Liouville derivative, and various fixed point theorems to develop optimal control results for functional differential systems with or without delay. The existence and stability of solutions for an optimal control problems derived from an integrodifferential equations with a compact control set in the space L1([0,b];X) studied in Reference 32.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Reference 34, the authors present a general formulation and solution strategy for fractional optimal control issues. The authors of References 7, 18, 21, and 35–40 used impulsive systems, Clarke subdifferential type, neutral integrodifferential systems, Hilfer fractional derivative, stochastic systems, Riemann–Liouville derivative, and various fixed point theorems to develop optimal control results for functional differential systems with or without delay. The existence and stability of solutions for an optimal control problems derived from an integrodifferential equations with a compact control set in L1false(false[0,bfalse];Xfalse)$$ {L}^1\left(\left[0,b\right];X\right) $$ studied in Reference 41.…”
Section: Introductionmentioning
confidence: 99%
“…with A 2 and A 3 n × n matrices whose elements belong to L 2 (−1, 0); B is a constant n × r matrix; and the control u is an L 2 -function [1]. Nowadays, many researchers have investigated neutral differential equations in Banach spaces [2][3][4]. This interest is explained by the fact that neutral-argument differential equations have interesting applications in real-life problems: they appear, e.g., while modeling networks containing lossless transmission lines or in super-computers.…”
Section: Introductionmentioning
confidence: 99%